2017
DOI: 10.1016/j.pbiomolbio.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The tale of SSB

Abstract: The E.coli single stranded DNA binding protein (SSB) is essential to all aspects of DNA metabolism. Here, it has two seemingly disparate but equally important roles: it binds rapidly and cooperatively to single stranded DNA (ssDNA) and it binds to partner proteins that constitute the SSB interactome. These two roles are not disparate but are instead, intimately linked. A model is presented wherein the intrinsically disordered linker (IDL) is directly responsible for mediating protein-protein interactions. It d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
126
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 69 publications
(128 citation statements)
references
References 65 publications
(92 reference statements)
2
126
0
Order By: Relevance
“…The C-terminal domain of SSB can be further subdivided into two subdomains: a sequence of approximately 54 residues comprising residues 116-170, that is known as the linker and, the last eight residues which are known as the acidic tip (Kozlov et al, 2015;Shereda et al, 2008). The linker contains several structural elements critical to its function, including PXXP motifs (Bianco, 2017;Bianco et al, 2017;Tan et al, 2017). Critical to SSB function, the PXXP motifs in the linkers of one tetramer bind to the OB-fold(s) present in a nearby tetramer thereby facilitating cooperative ssDNA binding (Bianco, 2017;Bianco et al, 2017;Tan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The C-terminal domain of SSB can be further subdivided into two subdomains: a sequence of approximately 54 residues comprising residues 116-170, that is known as the linker and, the last eight residues which are known as the acidic tip (Kozlov et al, 2015;Shereda et al, 2008). The linker contains several structural elements critical to its function, including PXXP motifs (Bianco, 2017;Bianco et al, 2017;Tan et al, 2017). Critical to SSB function, the PXXP motifs in the linkers of one tetramer bind to the OB-fold(s) present in a nearby tetramer thereby facilitating cooperative ssDNA binding (Bianco, 2017;Bianco et al, 2017;Tan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We proposed that the PXXP-OB fold interaction involving SSB is analogous to the SH3-PXXP binding that occurs in eukaryotic systems and have taken advantage of in RecG loading. 31,32 If the IDL-OB-fold model is correct, and if SSB tetramers are linked to one another on a single stranded DNA molecule, then it is likely that changes in the IDL would impact several DNA metabolic processes in which SSB is involved. To test this, we examined the activities of various enzymes in the presence of WtSSB and the linker deletion mutants used previously.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and genetic studies have shown that SSB and RPA protect the ssDNA from nucleases, eliminate secondary structure to enable recombinase loading, serve as DNA damage signalling complexes and promote recruitment of downstream factors 64,6671 (FIG. 1).…”
Section: Sm-based Insights Into Recombinationmentioning
confidence: 99%